(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Water is the one of the topmost gift natures granted to all living creatures. It plays vital role for surviving world. A good quality of drinking water is essentially for all the people throughout the world. Quality drinking water should have balanced pH, rich contaminants and toxin free, minerals occurring, healthy. Some physical and chemical parameters were used for examined pH, TDS, Total Alkalinity, Total hardness, Chloride, turbidity. Poor quality of drinking water hazardous for health, in the present investigation undertaken groundwater samples for detecting from two tahsils, were 185 villages involved, surrounding area water mostly use for drinking purpose, agricultural, industrial and domestic. Mostly reasserts are groundwater sources (natural water) which contain different impurities.